Is Trisomy 21 a Risk Factor for Rapid Progression of Pulmonary Arteriopathy? ― Revisiting Histopathological Characteristics Using 282 Lung Biopsy Specimens - Masaki, Naoki; Saiki, Yuriko; Endo, Masato; Maeda, Kay; Adachi, Osamu; Akiyama, Masatoshi; Kawamoto, Shunsuke; Saiki, Yoshikatsu (Circulation Journal, 2018)
Background:Pulmonary hypertension (PH) is more progressive in trisomy 21 patients. However, pulmonary arteriopathic lesions in these patients have not been fully characterized histopathologically.Methods and Results:A retrospective review of a lung biopsy registry identified 282 patients: 188 patients with trisomy 21 (Group D) and 94 without (Group N). The mean age at lung biopsy was 3 and 7 months (P<0.0001). Pulmonary arterial pressure (PAP) and pulmonary vascular resistance were similar between the 2 groups. There were no significant differences in the proportion of patients with irreversible intimal lesions or the index of pulmonary vascular disease (IPVD; a measure of the degree of pulmonary arteriopathy progression) between the 2 groups. In addition, after propensity score matching for patient background (n=43 in each group), there were no significant differences in IPVD (P=0.29) or the ratio of irreversible intimal changes between the D and N groups (P=0.39). Multivariate analysis identified age (P<0.0001) and PAP (P=0.03) as the only risk factors for progression of pulmonary arteriopathy.Conclusions:Histopathologically, early progression of pulmonary arteriopathy in patients with trisomy 21 was not proved compared with patients without trisomy 21. Although we cannot exclude the possibility of bias in the Group D and N patients who were slated for lung biopsy, factors other than pulmonary arteriopathy may affect the marked progression of clinical PH in trisomy 21 patients.